Psychological-pedagogical conditions of motivation development in foreign language teaching of engineering-pedagogical disciplines students. - Zelenin, G. (Problems of Engineer-Pedagogical Education, 2018)
This article analyses the terms "motive", "internal and external motivation. The psychological-pedagogical conditions of motivation development concerning to foreign language studying among students of engineering-pedagogical specialties are concerned and the different approaches of positive motivation formation, preservation and development of students concerning to the subject of "foreign language" are suggested, and the peculiarities of foreign language teaching of engineering-pedagogical specialties students, having negative effect on the educational process efficiency are defined. The technologies of pedagogical influence concerning to motivation development of foreign language studying: the technology of direct influence, the technology of synchronized influence, the technology of indirect influence are exposed in the given article. The correct interpretation and practical using of the given technologies can help the teacher to disclose the necessity of foreign language practical using in future professional activity, to educate in-depth approach to specialization choosing.